Goltz syndrome: A newborn with ectrodactyly and skin lesions - Shatanik Sarkar; Chaitali Patra; Amit Das; Sutirtha Roy (Wolters Kluwer Medknow Publications, 2015)
Goltz syndrome or Focal Dermal Hypoplasia is a rare multisystem disorder, involving all the three germ cell layers. The disease is thought to be inherited in X-linked dominant fashion with heterogeneous mutations of the PORCN gene at Xp11.23 locus. Majority of the cases are sporadic, mainly due to postzygotic somatic mutations. The clinical spectrum includes characteristic cutaneous manifestations, multiple skeletal anomalies, and involvement of the eyes, hair, nails, kidneys, and so on. Considerable variability is noted in the clinical expression of the disease probably due to genomic mosaicism. Around 300 cases of Goltz syndrome have been reported in the literature. Here, we report such a case with characteristic skin lesions, multiple bony defects, distinctive facial features, coloboma of iris, and bilateral hydronephrosis. The diagnosis was evident immediately after birth due to the characteristic clinical picture of the baby.